PERLINDUNGAN HUKUM TERHADAP PEMEGANG HAK PATEN DITINJAU DARI UU NO 14 TAHUN 2001 TENTANG HAK PATEN - Alifia Devi Erfamiati (Ganesha Law Review, 2021)
Intellectual property rights are rights to objects (especially immaterial objects) that come from the work of the brain in the form of thoughts or a combination of reason and empathy. Patent rights are one of the intellectual property related to the industrial sector.Patents are exclusive rights granted by the state to inventors for their inventions in the field of technology, which for a certain period of time carry out their own inventions or give their consent to other parties to implement them. Furthermore, an invention is an inventor's idea that is poured into an activity to solve specific problems in the field of technology, which can be in the form of a product or process, or improvement and development of a product or process. As one of the Intellectual Property Rights (HKI).